(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To evaluate the incidence of one year-mortality following hip surgery in elderly population. Methods: This study conducted from January 2012 to June 2015 and the data was extracted from the patients’ data registry. All patients> 60 years of age underwent surgery for hip fractures (femur neck, trochanteric and sub-trochanteric fractures) from January 2012 to June 2015 in orthopedic surgery department of Liaquat National Hospital were included. Results: Total of 385 patients operated for hip fractures (femoral neck, trochanteric, sub-trochanteric fractures) during follow up it was found 24 (6.2%) patients were died within 90 days of hip surgery, 57 (14.8%) expired within 6 months and 82 (21.3%) patients could not survived beyond one year after hip surgery. Cardiovascular disease found to be the leading cause of mortality among these patients 45(56.1%) Conclusion: –It was observed that higher rate of mortality in elderly population following hip surgery in our target population.